Hubungan antara Dimensi Calling dan Career Adaptability pada Guru SMA - Christine Christine; Missiliana Riasnugrahani (Humanitas (Jurnal Psikologi), 2021)
This study examines the relationship between the dimensions of calling and career adaptation in high school teachers "X" Foundation Bandung. Through the purposive sampling technique, we collected 66 teachers that worked for at least one year. The age range of teachers ranged from 24-67 years, and more than half were male. The measuring instruments used are the Calling and Vocation Questionnaire (CVQ) and the Career Adapt-Abilities Scale Short-Form (CAAS-SF), which have good reliability scores. Data processing with Pearson correlation analysis found that the dimensions presence of calling and career adaptability were significantly positively correlated. The results show that teachers who believe that work is a calling will be easier to adapt to changes and challenges in their work. Therefore, the school can encourage teachers to maintain and improve their calling to adapt well to their work. Keywords: Presence of Calling, Search for Calling, Career Adaptability, Teachers